Evolutionary and Structural Overview of Human Picornavirus Capsid Antibody Evasion - Cifuente, Javier Orlando; Moratorio, Gonzalo (Frontiers in Cellular and Infection Microbiology, 2019)
Picornaviruses constitute one of the most relevant viral groups according to their impact on human and animal health. Etiologic agents of a broad spectrum of illnesses with a clinical presentation that ranges from asymptomatic to fatal disease; they have been the cause of uncountable epidemics throughout history. Picornaviruses are small naked RNA-positive-stranded viruses which include some of the most important pillars in the development of virology, comprising Poliovirus, Rhinovirus, and Hepatitis A virus. Picornavirus infectious particles use the fecal-oral or respiratory routes as primary modes of transmission. In this regard, successful viral spread relies on the capability of viral capsids to (i) shelter the viral genome, (ii) display molecular determinants for cell receptor recognition, (iii) facilitate efficient genome delivery, and (vi) escape from the immune system. Importantly, picornaviruses display a substantial amount of genetic variability driven both by mutation and recombination. Therefore, the outcome of their replication results in the emergence of a genetically diverse cloud of individuals presenting phenotypic variance. The host humoral response against the capsid protein represents the most active immune pressure and primary weapon to control the infection. Since the preservation of the capsid function is deeply rooted in the virus evolutionary dynamics, here we review the current structural evidence focused on capsid antibody evasion mechanisms from that perspective.